Hubungan Ketersediaan Jamban, Perilaku, dan Pengetahuan Masyarakat Dengan Buang Air Besar (BAB) di Kelurahan Legok Kecamatan Danau Sipin Kota Jambi Tahun 2018 - Sondang Siahaan; Rina Fauziah (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Family toilet facilities in the community, especially in their implementation, are not easy, because they involve community participation which is usually very closely related to behavior, knowledge, and culture. Availability of latrines, behavior, and community knowledge can influence bowel movements. Based on data from the ayu putri community health center, the Legok village has the most cemplung latrines, 644 latrines. The purpose of this study was to determine the relationship between the availability of latrines, behavior, and community knowledge with defecation in Legok Village, Danau Sipin District, Jambi City. This type of research is analytic descriptive with cross sectional approach. This research was conducted with inclusion criteria. The sample in this study was 87 households. The results showed that the availability of latrines was 62 households while there were not 25 households, 37 KKs of good behavior while 50 kk of bad behavior, 59 kk of good knowledge while 28 KKs of unfavorable knowledge and 62 KKs in the latrine were 62 KK. while defecation in the river is 25 families. The conclusion is that there is a significant relationship between the availability of latrines, behavior, and community knowledge with BAB. Suggestions from this research are the community to make toilet arisan for making latrines and septic tanks aimed at people who do not have latrines and septic tanks.